Exponential Smoothing untuk Peramalan Jumlah Penjualan Hijab Vie Hijab Store - Eky Cahya Pratama; Muhammad Tanzil Furqon; Sigit Adinugroho (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
In the modern era like today, advances in information technology have penetrated into various fields, one of which is in the industrial sector which can assist in the decision-making process to forecasting something that will happen in the future. Vie Hijab Store is a home-based business, such as a sewing house, which is concerned in the production and sale of hijab, which has problems stocking fabric as raw material. The process of forecasting the number of sales will be very helpful in regulating the decision-making process when stocking goods. In this study, the method used for forecasting Exponential Smoothing which consists of Single Exponential Smoothing (SES), Double Exponential Smoothing (DES), Triple Exponential Smoothing (TES) methods. Referring to one of the test results on the 4th increase period data sample which represents the situation of an increase in the second year of the Hajj month obtained from the dataset, the best parameter values for khimar products in the TES method are alpha = 0,9, beta = 0,9 and gamma = 0,1 which resulted in a MAPE of 11.47%. As for pashmina products in the TES method with alpha = 0.4, beta = 0.9 and gamma = 0.8 which resulted in a MAPE of 9,22%. Based on the results of all the tests of the three methods, if a comparison is made, it is shown that the majority of the best results are obtained when using the Triple Exponential Smoothing method. Therefore, the Triple Exponential Smoothing method was chosen as the best method for forecasting the number of hijab sales.